UNDERSTANDING OF EMERGENCY SITUATIONS - Shermatova Yakutkhan Sabirovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides the general meaning and essence of the concept of an emergency situation, the causes of emergency situations, their prevention and elimination.